Management Strategies of Media Indonesia Daily Newspaper for Sustaining Its Existence in the Digital Era (Oratio Directa, 2022)
This study examines the management strategies used by Media Indonesia Daily to sustain its print newspaper in the digital era. A descriptive qualitative approach was applied through semi-structured interviews with four organizational actors: a humaniora editor, an assistant head of circulation and distribution, an assistant research-and-development editor, and a journalist. The findings identify five mutually supporting practices: print-digital convergence through online news and e-paper services; journalist training and professional development; paid and non-paid distribution channels; data-based reporting supported by the research-and-development unit; and verification procedures involving relevant sources, recordings, and editorial review. The organization frames digital media as both a challenge and an opportunity rather than as a reason to discontinue print. Print and digital products are positioned as complementary channels for serving different reader needs. However, the source does not report interview dates, a coding procedure, circulation figures, revenue trends, audience measurements, or independent documentary evidence. Consequently, the results describe participants' organizational accounts and cannot establish the commercial effectiveness or long-term sustainability of the strategies.
Keywords: Media convergence; Media management; Print media; Marketing strategy; Digital transformation